2017
DOI: 10.1002/anie.201702330
|View full text |Cite
|
Sign up to set email alerts
|

Native Mass Spectrometry from Common Buffers with Salts That Mimic the Extracellular Environment

Abstract: Nonvolatile salts are essential for the structures and functions of many proteins and protein complexes but can severely degrade performance of native mass spectrometry by adducting to protein and protein complex ions, thereby reducing sensitivity and mass measuring accuracy. Small nanoelectrospray emitters are used to form protein and protein complex ions directly from high-ionic-strength (>150 mm) nonvolatile buffers with salts that mimic the extracellular environment. Charge-state distributions are not obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 25 publications
1
106
0
Order By: Relevance
“…As a result, fewer sodium ions are enriched during the droplet desolvation of smaller initial droplets than larger droplets, resulting in lower sodium ion concentrations in “mature” ESI droplets prior to ion release. 3234…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, fewer sodium ions are enriched during the droplet desolvation of smaller initial droplets than larger droplets, resulting in lower sodium ion concentrations in “mature” ESI droplets prior to ion release. 3234…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of salt adduction and salt cluster formation can be attributable to the small initial droplet sizes produced by submicrometer ESI emitter tips, which results in a lower concentration of nonvolatile contaminants in ESI droplets prior to ion release. 33,34 To date, the binding affinities of noncovalent complexes have not been measured in solutions containing nonvolatile molecules and salts using ESI-MS. Thus, the effects of using nonvolatile buffers and metal ion salts, including those that are commonly employed to stabilize protein structure(s) on the measured ligand–protein binding constants in native MS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…29 Although several methods have been demonstrated that allow the native MS analysis of samples present in non-volatile buffers, we believe that OBE has advantages in speed, simplicity, and robustness. Whereas proteins can be directly ionized from non-volatile buffers via nano ESI when small diameter tips are used, [30][31][32] this procedure requires significant expertise and time to pull the proper tips, making it difficult to use as a routine method of analyzing dozens or even hundreds of samples. Additives, 33 electrolytes, 34,35 and supercharging reagents 36 can also help to counteract the effect of non-volatile buffer components on protein spectral quality, but their capability is generally limited to non-volatile concentrations lower than what would be used during protein purification, and the lack of non-volatile removal prior to ionization can increase the frequency of required instrument maintenance.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Generally, analytical separation, including microscale electrophoresis 15,18 , is an efficient strategy in many biological and chemical analyses of various target molecules, especially for peptides and proteins from complex biological samples 19,20 . To improve the separation efficiency and real sample applications, in situ analytical separation has been developed at microscale and even nanoscale in both time and space 15,1719 .…”
Section: Introductionmentioning
confidence: 99%